FIRE AND EXPLOSION RISK PREVENTION - Shermatova Yoqutxon Sabirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the Prevention of the risk of fire and explosion, as well as the presence of a large number of fire and explosion-prone objects in our Republic, which are sources of danger to the population and regions.